The age of the so-called "bostonite" rocks of Mórágy Hill, S-Hungary - Szabados Cs.; Árva-Sós Erzsébet (University of Szeged, Department of Mineralogy, Geochemistry and Petrology Szeged, 1996)
MAURTTZ and CSAJÁGHY (1952) could not define exactly the data of consolidation and the genetic origins of the rocks found in the Mórágy granite and which was named "bostonite" by them. These questions have not been answered since that. K/Ar isotopic age of these rocks may reflects that the consolidation happened parallely to that of the rocks of the Early Cretaceous alkaline volcanism.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok